Characteristics and Reach Equity of Policies Restricting Flavored Tobacco Product Sales in the United States. Issue 1 (January 2020) - Rose, Shyanika W.; Amato, Michael S.; Anesetti-Rothermel, Andrew; Carnegie, Brittany; Safi, Zeinab; Benson, Adam F.; Czaplicki, Lauren; Simpson, Randall; Zhou, Yitong; Akbar, Maham; Younger Gagosian, Stacey; Chen-Sankey, Julia Cen; et al.
In 2009, flavored cigarettes (except menthol) were banned in the United States, but other flavored tobacco products (FTPs) were allowed. Women, populations of color, youth, sexual minority, and low–socioeconomic status populations disproportionately use FTPs. Localities have passed sales restrictions on FTPs that may reduce disparities if vulnerable populations are reached. This study assessed the extent to which FTP restrictions reached these subgroups ("reach equity"). We identified 189 U.S. jurisdictions with FTP policies as of December 31, 2018. We linked jurisdictions with demographics of race/ethnicity, gender, age, partnered same-sex households and household poverty, and stratified by policy strength. We calculated Reach Ratios (ReRas) to assess reach equity among subgroups covered by FTP policies relative to their U.S. population representation. Flavor policies covered 6.3% of the U.S. population (20 million individuals) across seven states; 0.9% were covered by strong policies (12.7% of policies). ReRas indicated favorable reach equity to young adults, women, Hispanics, African Americans, Asians, partnered same-sex households, and those living below poverty. Youth, American Indians/Alaska Natives (AIAN) and Native Hawaiians/Pacific Islanders (NHPI) were underrepresented. Strong policies had favorable reach equity to young adults, those living below poverty, Asians, NHPIs, individuals of 2+ races, and partnered same-sex households, but unfavorable reach equity to women, youth, Hispanic, AIAN, and African American populations. U.S. flavor policies have greater reach to many, but not all, subgroups at risk of FTP use. Increased enactment of strong policies to populations not covered by flavor policies is warranted to ensure at-risk subgroups sufficiently benefit.